Students’ Perception of Vocabulary Learning Through Captions on Instagram - Andira, Ayu; Ariyani, Amra; Fauzan, Muh. Miftah (Journal of Excellence in English Language Education, 2025)
This study aims to find out students' perceptions of vocabulary learning through captions on Instagram. This research was conducted at SMP Negeri 2 Donri-Donri. This research used a qualitative descriptive method. Participants in this study were the 8th-grade students, and to obtain data, the researcher used interviews.  The result of this study is that the participants gave a good perception or good response. The participant’s reception, understanding, and evaluation that learning vocabulary by using captions on Instagram supported their learning vocabulary through captions on Instagram. This means that learning vocabulary through captions on Instagram received a good response from the students, so that it can be a good choice as an English learning media.